Treating child and adolescent anxiety effectively: Overview of systematic reviews. (December 2016) - Bennett, Kathryn; Manassis, Katharina; Duda, Stephanie; Bagnell, Alexa; Bernstein, Gail A.; Garland, E. Jane; Miller, Lynn D.; Newton, Amanda; Thabane, Lehana; Wilansky, Pamela
Abstract: We conducted an overview of systematic reviews about child and adolescent anxiety treatment options (psychosocial; medication; combination; web/computer-based treatment) to support evidence informed decision-making. Three questions were addressed: (i) Is the treatment more effective than passive controls? (ii) Is there evidence that the treatment is superior to or non-inferior to (i.e., as good as) active controls? (iii) What is the quality of evidence for the treatment? Pre-specified inclusion criteria identified high quality systematic reviews (2000–2015) reporting treatment effects on anxiety diagnosis and symptom severity. Evidence quality (EQ) was rated using Oxford evidence levels [EQ1 (highest); EQ5 (lowest)]. Twenty-two of 39 eligible reviews were high quality (AMSTAR score ≥ 3/5). CBT (individual or group, with or without parents) was more effective than passive controls (EQ1). CBT effects compared to active controls were mixed (EQ1). SSRI/SNRI were more effective than placebo (EQ1) but comparative effectiveness remains uncertain. EQ for combination therapy could not be determined. RCTs of web/computer-based interventions showed mixed results (EQ1). CBM/ABM was not more efficacious than active controls (EQ1). No other interventions could be rated. High quality RCTs support treatment with CBT and medication. Findings for combination and web/computer-based treatment are encouraging but further RCTs are required. Head-to-head comparisons of active treatment options are needed. Highlights: Overviews of systematic reviews facilitate evidence-informed decisions about anxiety treatment options for children and youth. High quality RCTs support treatment with CBT and medication. Findings for combination and web/computer-based treatment are encouraging but further RCTs are needed. Head-to-head comparisons in RCTs of active treatment options are needed. Many relevant systematic reviews have avoidable methodologic weaknesses.